Diseño de barras y tablero de distribución eléctrica secundaria, para mejorar la capacidad de carga en la Universidad Técnica de Cotopaxi – La Maná año 2012 - Martínez Reyes, Luis David (2014)
The present research work was developed in order to improve the quality of electric service within the Cotopaxi Technical University La Maná which was deteriorated due to the lack of continuous maintenance and obsolete electrical installations that were replaced. In addition, the problem of frequent power cuts was affecting the students’ academic performance because most of them execute their academic activity in the evening hours; so the main goal of this project was the implementation of an electric generator that supplies power to the frequent power cuts.